Preferential associations in an unstable social network: applying social network analysis to a dynamic sow herd - Jowett, Sarah L.; Barker, Zoe Elizabeth; Amory, Jonathan R. (Frontiers in Veterinary Science, 2023)
Preferential associations are fitness-enhancing ties between individuals, documented in a range of taxa. Despite this, research into preferential associations remains under-represented in commercial species, particularly pigs. This study investigates the development of preferential associations in a dynamic sow herd. Preferential associations were defined as approaching a resting sow and then sitting or lying with physical contact to selected sow, separated by ˂ 1m from the head or directly next to her, with interaction tolerated for > 60 s. For individual identification, each sow was marked with coloured dots, stripes, or both, corresponding to their ear tag number. Preferential associations were measured over one production cycle of 21 days. Behavioural observations occurred on seven days of the study, recording 3 hours of behaviour per day during peak activity times (08:00 – 09:00, 15:00 – 16:00, 20:00 -21:00 h). Behaviours were recorded using five cameras, each positioned within the barn to provide coverage of the functional areas. The network metrics applied included indegree centrality (received ties), outdegree centrality (initiated ties), centralisation (the extent to which an individual is central within the network), clustering coefficient (a measure of tie strength) and, the E-I Index (a measure of assortment by trait: parity, familiarity, and sociality). Individuals were added and removed during the study, so the centrality metrics of missing sows were weighted. To describe the structure of the network, brokerage typologies were applied. Brokerage typologies include five positions including coordinators, gatekeepers, representatives, consultants, and liaisons. Results revealed social discrimination in assortment by connectedness even when ties were unreciprocated, the most connected sows were significantly preferable to approach than lower connected individuals. The most connected sows had significantly higher indegree and outdegree centrality. With the application of brokerage typologies, results showed a relationship between connectedness and brokering type, with the highest connected sows predominantly engaging in coordinating behaviour. Results indicate the motivation for discrimination in the unstable preferential association network was not founded upon bi-directional interactions. These findings highlight the complexities involved when forming social preferences and present a platform for further exploring the motivations for preferential associations between intensively farmed pigs.